Designing plastic parts for assembly - Tres, Paul A. (Hanser Publishers, 2024)
For 30 years, Designing Plastic Parts for Assembly has been the definitive guide for both seasoned part designers and novices to the field, facilitating cost-effective design decisions and ensuring the longevity of plastic parts and products under use. This edition includes an extensive revision of the chapter on welding techniques.
Keywords: Plastics -- Molding.; Machine parts.; elektronické knihy; electronic books